Correlations of Motion Characteristics and Kinematic Attributes of Fresh and Frozen-thawed Spermatozoa of Gir Bulls - Pathak, PK; Dhami, AJ; Chaudhri, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This investigation was carried out on semen of three healthy mature breeding bulls of Gir breed to evaluate the interrelationships among sperm quality attributes of fresh and frozen-thawed semen assessed by Biovis CASA. The ejaculates (n = 24) having >75% initial motility were diluted @80 million sperm/mL using TFYG extender, filled in French mini straws, and were frozen using a programmable bio freezer after 4 hours of equilibration. The straws were thawed in a water bath at 37°C for 30 sec. The freshly diluted and frozenthawed samples were assessed for routine subjective tests and various motion characteristics/kinematics by Biovis CASA. The Pearson’s correlations for sperm motility and velocity/kinematic parameters of total motile sperm as well as of progressively motile sperm were studied in freshly diluted and frozen-thawed semen. In fresh semen, total motile sperm assessed by CASA had significant (p <0.05, 01) correlations with rapid progressive motile sperm (r = 0.46), wobbling index (r = 0.52) and dancing frequency (r = -0.43) in fresh semen. In frozen-thawed semen, it was significantly correlated only with linearity (r = 0.46). The rapid progressive motile sperm in both fresh (r = 0.41 to 0.92) and frozen-thawed (r = 044 to 0.88) semen, however, had significant correlations with most of their velocity traits. Further, the average path velocity (VAP), curvilinear velocity (VCL), straight line velocity (VSL), linearity (LIN), straightness (STR), wobbling (WOB), beat-cross frequency (BCF), amplitude of lateral head displacement (ALH), and dancing mean (DNM) of sperm showed significant positive or negative interrelationships among each other in both fresh (r = 0.41 to 0.91) as well as post-thawed (r = 0.44 to 0.90) semen. Moreover, the correlations of motility and kinematics parameters of total motile sperm in both fresh and frozen-thawed semen were highly significant with velocity/kinematics traits of only progressively motile sperm, and the velocity traits among only progressively motile sperm were highly significantly interrelated in both fresh (r = 0.46 to 0.98) and frozen-thawed (r = 0.43 to 0.93) semen of Gir bulls, though the magnitudes of correlations were lower in frozen-thawed semen as compared to fresh semen. Thus, CASA analysis of fresh semen for motility and velocity traits could predict the post-thawed sperm motility and velocity/kinematics of bovine semen.